2020
DOI: 10.1002/jmv.25697
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus burden improves a predictive model identifying measures of vascular risk in renal transplant recipients and healthy adults

Abstract: Cytomegalovirus (CMV) has been implicated in vascular pathologies and may warrant inclusion in cardiovascular predictive algorithms. We addressed this in healthy older adults and renal transplant recipients (RTR) as they retain a high burden of CMV. RTR (n  =  45) stable more than 2 years after transplantation and 58 age‐matched healthy adults were assessed. Plasma inflammatory biomarkers (soluble isoform of the interferon‐β receptor [sIFNAR2], soluble tumour necrosis factorreceptor‐1 [sTNFR1], soluble cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This could begin with R267K, as the variant was associated with increased gB-reactive antibody levels in RTR and a healthier FMD (i.e., better endothelial function). Accordingly, a previous study of the same cohort revealed that levels of gB-reactive antibodies were protective of FMD, as assessed in a 3-year follow up ( 40 ). Our data suggest that variants carrying R267K may promote this protective response.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This could begin with R267K, as the variant was associated with increased gB-reactive antibody levels in RTR and a healthier FMD (i.e., better endothelial function). Accordingly, a previous study of the same cohort revealed that levels of gB-reactive antibodies were protective of FMD, as assessed in a 3-year follow up ( 40 ). Our data suggest that variants carrying R267K may promote this protective response.…”
Section: Discussionmentioning
confidence: 92%
“…Ultrasonography was used to assess FMD of the brachial artery after 10 min of rest in Australian RTR and healthy controls ( 40 ). FMD assesses the ability of the larger conduit artery to respond to shear stress via endothelial-dependent and endothelial-independent mechanisms.…”
Section: Methodsmentioning
confidence: 99%
“…FMD associated inversely with levels of sTNFR in healthy controls, with a weak protective effect of gB antibodies. gB also marked protection in our search for biomarkers that predict FMD measured in Australian renal transplant recipients after an interval of three years [ 22 ]. The association is plausible because CMV gB is considered a protective antigen based on its critical role in mediating viral-host cell fusion and thus viral entry.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the transient expression of HCMV DNA in clinical samples. T-cell responses to HCMV IE-1 have been linked with frequent reactivations of HCMV as IE-1 is the first protein expressed during viral replication, but they build over time and so are elevated in HIV patients stable on antiretroviral therapy (ART) [ 7 ]. Our results would be consistent with persistent low-level HCMV replication in the acinar cells of the salivary gland, with episodic outbreaks stimulating systemic responses to HCMV IE-1.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, renal transplant recipients (RTR) have higher levels of circulating antibodies than the general population [ 6 ]. Interferon γ-producing T-cells, particularly those specific for HCMV Immediate Early 1 (IE-1) antigen, are also increased in RTR [ 7 ]. Responses to this antigen are also elevated in HIV patients [ 8 ] and are thought to reflect frequent reactivations of HCMV as the antigen is produced in the earliest stages of the replicative cycle [ 9 ].…”
Section: Introductionmentioning
confidence: 99%